THE MEDIATING EFFECT OF TACIT KNOWLEDGE SHARING IN PREDICTING INNOVATIVE BEHAVIOUR FROM TRUST - Nur Constance, Wah; Dahlia, Zawawi; Raja Nerina, Raja Yusof; Murali, Sambasivan; Jalina, Karim (International Journal of Business and Society, Faculty of Economics and Business, UNIMAS, 2018)
The recent COVID-19 has significantly impact the awareness towards importance of online shopping in Malaysia. Nevertheless, the online shopping adoption rate in Sarawak particularly in Sibu is relatively low at only 24 percent of its total population. With the recent development of e-commerce, the types of consumers to adopt online shopping have becoming more diverse than before. This research incorporates the Theory of Planned Behaviour (TPB) and demographic determinants to provide insights on the acceptance and adoption of online shopping among consumers in Sibu, Sarawak. Five hypotheses were developed accordingly to evaluate the relationships of proposed framework model. A web-based survey was employed to minimize the physical contact with the respondents. A total of 384 respondents were selected in order to represent the population of Sibu, of which only 308 samples were acceptable for analysis. Responses were analyzed using Mann-Whitney U Test and Kendall’s Tau b-Test. The results showed all the independent variables (age, gender, education level, and attitude) have significant effect on the behavioral intention. On the other hand, age factor was found to be negatively related to attitude and behavioral intention of online shopping. Furthermore, the finding indicates that behavioral intention was positively related to the actual usage behavior of online shopping. These results suggest that the e-commerce platform developers and e-marketers are responding to consumers’ acceptance including the adoption of online shopping.